Legal Research Method: Theoretical and Implementative Review - Hamzani, Achmad Irwan; Widyastuti, Tiyas Vika; Khasanah, Nur; Rusli, Mohd Hazmi Mohd (International Journal of Membrane Science and Technology, 2023)
Legal research has methods like research in general. The process of legal research is adjusted to the legal events that occur. Legal research can be seen from various aspects. The purpose of writing this article is to describe the types, approaches, research data, data collection techniques, and data analysis methods in legal research. This research uses a conceptual approach which is still within the scope of the normative approach because it only examines the opinions that develop in the research method. The results of this study indicate that the type of legal research is divided into field research using primary data and library research using secondary data. Approaches in legal research are divided into normative, empirical, and philosophical approaches. Data in legal research is grouped into primary data which is obtained directly, and secondary data which is referred to as legal material. Data collection techniques depend on the type of research and data; Primary data was collected through observation, interviews, questionnaires, participation, and experimentation. Secondary data was obtained through offline and online searches. Methods of data analysis can be done qualitatively and quantitatively. Qualitative data analysis used content analysis, narrative analysis, discourse analysis, and interactive analysis methods. Quantitative data analysis using descriptive analysis method and inferential analysis method.